The Inclusion of Children with Intellectual Disability and Homeless Children: A Comparative Look between Chile, Colombia, and Mexico - Corona Gaona, Fabiola Yuzeth (2017)
Based on a research project about the topic of diversity, conducted by the academic team to which the third author of this article belongs, there was a concern to inquire about how support is being provided to children and adolescents in vulnerability condition in other Latin-American countries. To achieve this, we made a bibliographical review; it is the intention of this text to carry out a comparative analysis among the countries of Chile, Colombia, and Mexico, with respect to the approach they hold regarding educational inclusion. At the same time, there will be a description of one case for each of the countries about ways in which children and their families live in vulnerability conditions; the Mexican example arises from an intervention performed by one of the authors of this article. Based on the comparison made, there are proposals for improvement for the Mexican program of educational inclusion.